Technical efficiency and productivity growth analysis of aquaculture of Peninsular Malaysia - Iliyasu, Abdullahi (2014)
The demand for animal protein especially fish is expanding due to the population growth, increased incomes, and changes in eating habits and life styles. The capture fisheries in Malaysia which supply over 70% of the fish used for food are over-exploited and the yield has become stagnant over the last decades and in some cases it has even declined. In addition, the balance of trade for the past decade has been negative signaling a threat to the economic growth. However, aquaculture has the potential to meet these challenges if it is well practiced. This can be done through intensifying production levels which require a high usage of inputs though it may lead to technical inefficiency and increase the production costs of the farmers. This can ultimately make them to abandon the farms and opt for alternative sources of income due to low profits or losses. Hence, there is a need to improve the inputs usage efficiency as well as increase productivity in aquaculture. The study, therefore, aims to estimate the Slack Based Measure (SBM) of technical efficiency and evaluate the determinants of technical inefficiency in aquaculture. The study aims to compute the Total Factor Productivity (TFP) growth and its components. In addition, it aims to identify the sources of TFP growth in aquaculture. Data Envelopment Analysis (DEA) Malmquist Productivity Index, and regression model have been employed to analyze data. Three states have been selected for the studies because of their high production levels and active fish farmers. Data from 248 fish farms were collected using well structured questionnaires and oral interviews. The estimated mean technical efficiency scores for ponds, tanks, cages and pen production technology were estimated to be 0.86, 0.91, 0.97 and 0.94, respectively. The findings show that the technical efficiency scores are relatively high for the sample fish farmers, which indicate that there is little room for improvement in the production. All the input variables revealed presence of slacks, an indication of inefficiency. The second-stage DEA analysis shows that factors such as experience, extension services, workshops attended and water management are found to have positive significant impact on technical efficiency. Furthermore, the TFP growth was estimated to be 3.7%, indicating progress in the productivity. However, this figure was less than average annual production growth of 10%. Accordingly, the contribution of Technological Change (TC) and Efficiency Change to Total Factor Productivity Change (TFPC) was 1.9% and 1.8%, respectively. Therefore, increment of TFPC should be geared towards both improving the managerial skills of farmers as well as introduction of new and improved technology. Information on factors influencing technical efficiency should be disseminated to farmers by the extension agents to reduce production inefficiency. Government should provide some water quality analyzing tools as an incentive to fish farmers for testing water quality at affordable rate. This will help in reducing mortality rate as well increasing production. Research towards improving production technologies should be encouraged by the government through provision of easy access to grants and other relevant facilities necessary to improves productivity.